The neural correlates of hedonic and eudaimonic happiness: An fMRI study. (1st November 2019) - Costa, Tommaso; Suardi, Angelo Carlo; Diano, Matteo; Cauda, Franco; Duca, Sergio; Rusconi, Maria Luisa; Sotgiu, Igor
Highlights: Imagination of both hedonic and eudaimonic events activated a common neural network. Shared neural correlates included cingulate cortex, temporal gyrus, and cerebellum. Both events were also associated with distinct brain areas serving diverse functions. Hedonic activation was greater in frontal gyrus and anterior cingulate cortex. Eudaimonic activation was greater in right precentral gyrus. Abstract: The current study investigated the neural correlates of both hedonic and eudaimonic happiness. Seventeen students underwent fMRI while cued with written sentences describing three classes of life events: Hedonic events (HE), eudaimonic events (EE) and neutral events (NE). We asked participants to imagine and empathize with all these event types. Results showed that, compared to NE, both HE and EE activated a network involving frontal, temporal and parietal regions, as well as subcortical structures. However, in the HE/EE comparison, HE showed enhanced activity in frontal medial/middle regions and anterior cingulate cortex; by contrast, EE showed increased activity in the right precentral gyrus. Findings suggest that hedonic and eudaimonic happiness activate similar neural correlates. However, both kinds of happiness are also associated with distinctive brain areas serving distinctive functions.